Epithelial–mesenchymal transition in lung development and disease: does it exist and is it important?. Issue 8 (12th December 2013) - Bartis, Domokos; Mise, Nikica; Mahida, Rahul Y; Eickelberg, Oliver; Thickett, David R
Abstract : Epithelial–mesenchymal transition (EMT) is a process when epithelial cells gradually transform into mesenchymal-like cells losing their epithelial functionality and characteristics. EMT is thought to be involved in the pathogenesis of numerous lung diseases ranging from developmental disorders, fibrotic tissue remodelling to lung cancer. The most important question—namely what is the importance and contribution of EMT in the pathogenesis of several chronic lung conditions (asthma, COPD, bronchiolitis obliterans syndrome and lung fibrosis)—is currently intensely debated. This review gives a brief insight into the mechanism and assessment methods of EMT in various pulmonary diseases and summarises the recent literature highlighting the controversial experimental data and conclusions.